IMPLEMETASI HUKUM KELUARGA ISLAM PADA UNDANG-UNDANG PERKAWINAN DI INDONESIA MENGENAI HAK MEMILIH PASANGAN BAGI PEREMPUAN - Arif Sugitanata; Suud Sarim Karimullah (Center of Gender Studies and Child of State Islamic Institute of Metro, 2023)
This paper discusses the implementation of Islamic family law in Indonesia's marriage law regarding the right to choose a partner for women with the main problem explaining how the interrelationships of the values ​​of Islamic family law are absorbed in Indonesian laws. Utilizing a literature study whose primary data sources come from books, journals and statutes, this research finds that Indonesia, as a country known for its Muslim majority and having many ethnicities and cultures, also adopts the principles of equality in Islam implemented in Marriage Law No. 1 of 1974 is included in the realm of choosing a mate for women. As stipulated in UUP No. 1 of 1974 concerning the conditions for marriage regulated in Article 6 Paragraph 1, namely that there must be the consent of the bride, meaning that the woman is willing to be married by a man who wants to marry her without any coercion. What is contained in Article 6 Paragraph 1 UUP No. 1 of 1974 is in line with the mission of Islam, namely the principle of equality for women. This aims to build a happy and eternal household and of course in line with human rights.